Practical Theology for Women How knowing God makes a difference in our daily lives - Alsup, Wendy Horger (Wheaton Crossway Books, 2008)
Have you ever wanted to understand the deep things of the Word but been put off by the intimidating vocabulary of theologians? Have you assumed that studying the attributes of God is for seminary students only? Or maybe just for men? Have heavy doctrina
Keywords: Christian women -- Religious life. Theology, Practical. RELIGION -- Christian Life -- Women's Issues. RELIGION -- Christian Life -- General